ANALISIS PENYUSUTAN KENDARAAN EKSAVATOR PADA PT. DHARMA JAYA BHAKTI DI BALIKPAPAN - Ariani, Dinda Noveranica (EKONOMIA, 2012)
The purpose of this research is to investigate the determination of the activa fixed assets depreciation by the use of servise hours method. Based on the analysis and the discussion, it can be generated that the proposed hypothesis is proven or acceptable under these following circumstances: The calculation analysis result for more appropriate depreciation method is the servise hours method due to the company that engage in the rental of heavy equipment vehicles with hourly rental system. The servise hour method of excavator depreciation vehicle at PT. Dharma Jaya Bhakti Balikpapan is : Rp. 1.220.000.000 excavator cost per unit x 5 unit = Rp. 6.100.000.000. The approximate estimated economic life is 10 years and it can work about 80.000 hours. The calculation of servise hours method is gained by a formula, the calculated cost reduced by the residual cost divided by estimated hours of actual servise. The depreciation with the servise hours method at PT. Dharma Jaya Bhakti Balikpapan that lasts for five years is Rp. 2.383.346.250 with the total hours of working vehicle is 173.600 hours. In this method, the depreciation is calculated on the basis of unit of servise hour. The expense of periodic depreciation will depend on the hours of servise in use (used) . By far the company has not calculated the vehicle depreciation, the management only uses predictions in determining the estimated economic life of the vehicle, so it does not know the actual profit. Some suggestions are proposed to use of the depreciation method of the active fixed assets especially for the vehicle on the next research that it will use the appropriate workable depreciation method that contribute to profit